Pengaruh Pelatihan Dan Motivasi Terhadap Produktivitas Kerja Karyawan Produksi Pada PT. Sukses Makmur Plastindo Tangerang : Pengaruh Pelatihan Dan Motivasi Terhadap Produktivitas Kerja Karyawan Produksi Pada PT. Sukses Makmur Plastindo Tangerang - Agus Sugiyanto Agus (PT. Karya Inovatif Nusantara, 2025)
This study aims to analyze and determine the effect of training and motivation on the workproductivity of production employees at PT. Sukes Makmur Plastindo. This research is a type ofdescriptive research with a quantitative approach method and by distributing questionnaires filledout by 93 respondents as a research instrument, while the data sources used are primary dataand secondary data. Besides that, in taking a data, the writer also uses validity test, reliability test,normality test, partial correlation analysis test, coefficient of determination test, multiple linearregression analysis, t test and F test. The results of the t (partial) analysis test on the Trainingvariable (X1) has an influence on the Work Productivity variable (Y) where the value of tcount =2.861 > ttable = 1.986 with a significance level of 0.000 is 0.316 or 31.6%. As for the results ofthe t-test analysis (partial) on the variable Motivation (X2) it also has an influence on the WorkProductivity variable (Y) where it is obtained that tcount = 4.692 > ttable = 1.986 with a significancelevel of 0.000 which is 0.518 or 51.8%. Based on the results of the ANOVA test, the value ofFcount = 78.256 > Ftable 3.10 with an Adjusted R Square value of 0.541 or 54.1%, the results ofthis study prove that, on the variable Training (X1) Motivation (X2) simultaneously has a significantinfluence on productivity Work (Y).Keywords: training, motivation, work productivity.